2017
DOI: 10.1007/s12035-016-0366-5
|View full text |Cite
|
Sign up to set email alerts
|

SVCT2 Is Expressed by Cerebellar Precursor Cells, Which Differentiate into Neurons in Response to Ascorbic Acid

Abstract: Ascorbic acid (AA) is a known antioxidant that participates in a wide range of processes, including stem cell differentiation. It enters the cell through the sodium-ascorbate co-transporter SVCT2, which is mainly expressed by neurons in the adult brain. Here, we have characterized SVCT2 expression in the postnatal cerebellum in situ, a model used for studying neurogenesis, and have identified its expression in granular precursor cells and mature neurons. We have also detected SVCT2 expression in the cerebellar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 45 publications
4
31
0
Order By: Relevance
“…Similar results were obtained by Oyarce et al. () in mouse Purkinje cells. Finally, in both species, strong immunostaining was observed in neurons of cortex and hippocampus, although the patterns were not perfectly aligned.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar results were obtained by Oyarce et al. () in mouse Purkinje cells. Finally, in both species, strong immunostaining was observed in neurons of cortex and hippocampus, although the patterns were not perfectly aligned.…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, no immunoreactivity was observed in the hypothalamus or the cerebellum in the present study, whereas intense SVCT2-IR was observed in many hypothalamic nuclei and in the Purkinje cell layer in the rat. Similar results were obtained by Oyarce et al (2017) in mouse Purkinje cells. Finally, in both species, strong immunostaining was observed in neurons of cortex and hippocampus, although the patterns were not perfectly aligned.…”
Section: Distribution Of Svct2supporting
confidence: 88%
See 2 more Smart Citations
“…Many studies indicate that SVCT2 is a transporter that is preferentially expressed in neurons from different areas in the adult brain, such as the cortex, hippocampus, hypothalamus, and cerebellar precursors [1,[7][8][9][10][11]. SVCT2 mediates uptake of AA, an important molecule for antioxidant defense and general metabolic needs of neurons.…”
Section: Distribution and Function Of Svct2 In The Adult Brainmentioning
confidence: 99%